Convergência incondicional e absoluta de séries em espaços de Banach - Herminio, Anderson de Farias (2022)
In this work, we study some of the main results of the theory of unconditionally summable sequences. We start with Dirichlet’s and Riemann’s theorems, which are in the context of real numbers, and move on to some results in the context of Banach spaces, emphasizing Macphail’s and the Dvoretzky–Rogers theorems.